Effects of therapies for temporomandibular disorder on the craniocervical posture: A randomized clinical trial (Research, Society and Development, 2021)
Objective: The present study searched evaluate whether the occlusal splint, physiotherapy and counseling therapies used in the treatment of temporomandibular disorders (TMD) alter the craniocervical posture and pain. Methods: Controlled, randomized, blinded study that included individuals previously diagnosed with TMD through the RDC/TMD (Research criteria for temporomandibular disorders). The patients were randomly selected from four treatment groups: occlusal splint (OS, n = 17), physiotherapy (P, n = 19), counseling (C, n = 15) and occlusal splint associated with counseling (OSC = 14), totaling 65 individuals. For the postural analysis, a teleradiography was performed at the baseline and 1 month after the application of the therapy, in order to observe the occiput-atlas distance (OAD), the craniocervical angle (CCA) and the positioning of the hyoid triangle (HT). CorelDraw X6 software (2012 Corel Corporation, Canada) was used in the images. The data obtained was submitted to several paired T tests (α = 5%) and for the pain variable the SPANOVA test was applied. Results: Except for the OSC group in the CCA variable (p = 0.003), the results showed that there was no statistically significant difference for the analyzed variables regarding the different therapies over time. However, it can be observed that all the treatment groups allowed a reduction of the patients' pain (p = 0.013) over time. Conclusion: It is concluded that the therapies applied have little influence on craniocervical posture but are effective for the relief of painful symptoms.